Variation in morphological characteristics of Japanese fluvial sculpin related to different environmental conditions in a single river system in eastern Japan. Issue 2 (14th March 2013) - Natsumeda, Takaharu; Tsuruta, Tetsuya; Takeshima, Hirohiko; Awata, Satoshi; Iguchi, Kei'ichiro
Abstract Stream fish with low mobility are often restricted to a narrow range of a stream course, and their morphological characters tend to be affected substantially by the environmental conditions of their habitat. We examined the relationships between environmental conditions and morphological characters of Japanese fluvial sculpin (Cottus pollux), a small, benthic fish with low mobility, at seven tributaries of the same river system in eastern Japan. Discriminant function analysis (DFA) indicated significant morphological differences in sculpins amongst the seven tributaries, and over 80% of individuals were classified correctly in each tributary. The strong positive correlation/loadings on the first discriminant function (DF1: 49.9% of total variation) were anterior caudal peduncle depth (0.436) and caudal peduncle truss (0.387), both of which could be regarded as an attribute of caudal peduncle depth. The second discriminant function (DF2: 16.5% of total variation) had a high negative loading for distance between the posterior first dorsal fin and anterior anal fin (−0.454), which could be regarded as an attribute of body depth. Correlation analysis indicated that sculpin tended to have a lower caudal peduncle depth under faster bottom current velocities at the tributary scale. Individuals deviating substantially from the centroid of DF2 in each tributary had a poorer body condition. Our results suggest the possibility of changes in the morphological characters of Japanese fluvial sculpin in relation to environmental conditions even at the tributary scale within the same river system.